Copper isotope evidence for recycled crustal sulfides in deep mantle plume source - Junhua Yao; Wei Yuan; Zhengrong Wang; Frédéric Moynier; Wei-Guang Zhu; Ya-Dong Wu; Yuchen An; Jiubin Chen (Communications Earth & Environment)
Abstract Earth’s crustal materials are recycled into the mantle through subduction, but the depth and nature of recycled components remain debated. Here we report copper (Cu) isotope evidence for the involvement of recycled crustal materials in a deep-mantle plume source. Permian mantle plume-derived picrites and basalts from the Emeishan large igneous province (Southwest China), excluding three hydrothermally altered outliers, exhibit δ65Cu values up to 0.65‰, obviously higher than typical mantle values (0.07 ± 0.10‰). The δ65Cu values show no correlation with loss-on-ignition (LOI), Mg#, ƐNd(t), Cu/Th, Cu/Pd, or redox state, ruling out magma differentiation or post-magmatic alteration. Instead, the elevated δ65Cu values most plausibly reflect recycled crustal sulfides with elevated δ65Cu value in the mantle source. These findings provide robust evidence for the recycling of Cu-rich sulfides into the deep mantle (potentially the lower mantle), elucidating the ultra-deep geochemical cycling of copper and sulfur within Earth’s interior.